RECOMMENDATIONS FOR VISUAL COMMUNICATION STRATEGY TO CHOOSE CLOTHES THAT FIT FOR WOMAN'S BODY SHAPE - Kusuma, Bryan Robert; Verina, Verina; Siagian, Marsaulina Syalom (Kohesi: Jurnal Sains dan Teknologi, 2025)
Choosing clothes that suit women’s body shape has the potential to not only for their comfort needs, but can also increase their self-confidence through wearing the right clothes. The purposes of designing this visual media project is to provide education to late teens girls from 18 to 21 years old about various female body shapes, and also providing clothing references idea as an information guide and style exploration based on each body shape. The methods that used for collecting data are interviews, questionnaire surveys, literature studies, and internet searches. For the design process, the method used is design thinking according to Stanford D. School, which includes empathize, define, ideate, prototype, and test. The Action Spurs method by Adam Ferrier was used, especially the Motivation Action Spurs Play. This approach is carried out by conveying information and insight about body shape through interesting and fun media. Fun interactive content is also provided through social media platforms. The "How to Say" concept in this project use SAEG FOR THE PROBLEM, which includes visualization and information about various types of women's body shapes and SHOW THE NEED, which presents visual communication media as a reference for clothing variations that suit body shape. Keywords: Body Shape, Clothing, Reference.